Freemasonry and Cosmopolitanism in Nineteenth Century Uruguay - Cano Roa, Efrain (2018)
This unpublished research on the socio-occupational relations and origins of the Uruguayan masons of the 19th century aims to reveal the social bases of Uruguay’s Freemasonry. The main documentary sources used were extracted from the main archives of the country together with internal documents of Freemasonry. The structure of the work revolves around the study of three periods, analyzing the nationality, occupations, geographical distribution of lodges and predominance of certain groups in the masonic workshops in order to try to answer the following question: who really integrated freemasonry in 19th Century Uruguay?